The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1097/00007890-198906000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Artery Thrombosis After Pediatric Liver Transplantation—a Medical or Surgical Event?1

Abstract: terns of antigenic expression on the surface of human monocytes lymphocyte subsets in long-term survivors with renal allotranand macrophages defined by monoclonal antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
143
3
10

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(159 citation statements)
references
References 15 publications
(7 reference statements)
3
143
3
10
Order By: Relevance
“…Technical improvements and the use of perioperative heparin or dextran may contribute to decreasing frequency of hepatic artery thrombosis in recent years. 11,12 As shown in this study, LD grafts also experience significant vascular complications.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Technical improvements and the use of perioperative heparin or dextran may contribute to decreasing frequency of hepatic artery thrombosis in recent years. 11,12 As shown in this study, LD grafts also experience significant vascular complications.…”
Section: Discussionmentioning
confidence: 55%
“…Hepatic artery thrombosis was responsible for over 50% of the grafts lost in these young children and accounted for a large portion of the decreased survival. 8 Mazzaferro et al 11 demonstrated a higher incidence of hepatic artery thrombosis if donor arteries were less than 3 mm diameter. Technical improvements and the use of perioperative heparin or dextran may contribute to decreasing frequency of hepatic artery thrombosis in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic artery thrombosis (HAT) is a cause of morbidity and graft loss in approximately 7% (range, 4% to 25%) of adults with an orthotopic liver transplant. [1][2][3] HAT is reported to occur in 10% to 40% [4][5][6] of pediatric patients receiving a primary liver transplant. This disparity occurs because of smaller caliber donor and/or recipient arteries and greater postoperative fluctuations in coagulation factor concentrations and hematocrits in children.…”
mentioning
confidence: 99%
“…This disparity occurs because of smaller caliber donor and/or recipient arteries and greater postoperative fluctuations in coagulation factor concentrations and hematocrits in children. 5 In adults, such potential risk factors as abnormal arterial anatomy of the donor or recipient arteries, technical complications during reconstruction, or such predisposing anatomy as the presence of a compressing median arcuate ligament 7 are increasingly rare because many are prevented by reconstructive techniques.…”
mentioning
confidence: 99%
“…Such changes have been known and studied in animals and humans for more than 30 years. 1,2 In particular, hepatic artery thrombosis (HAT) and other vascular complications (hepatic artery stenosis [HAS], portal vein thrombosis [PVT] and deep vein thrombosis [DVT]) remain devastating complications after LT. 2,3 The reported incidence of HAT is estimated to be 25% in living related allografts, 4 10% to 25% in pediatric cadaver liver recipients, [5][6][7][8] 2.6% to 20% in adult cadaver liver recipients, 9 and as high as 30% in children younger than 1 year old. 10 Early onset HAT usually develops within the first 2 months, 11,12 especially the first 5 days after LT. 13 Clinical presentations include acute, massive hepatic necrosis leading to fulminant hepatic failure, relapsing bacteremia with recurrent biliary sepsis from cholangitis, biliary tract ischemia leading to bile duct necrosis and leaks, and asymptomatic presentation with normal liver function tests.…”
mentioning
confidence: 99%